Posttraumatic Bilateral Basal Ganglia Infarct in Pediatric Age—Clinical and Therapeutic Management: A Rare Case Report and Review of Literature - Tarun Varshney; Vinod Sharma; Achal Sharma (Indian Journal of Neurosurgery)
Ischemic stroke of basal ganglia after head trauma is rare in children younger than 18 months and accounts for less than 2% of all ischemic strokes in childhood. The clinical history of these lesions is particularly favorable because they are usually small and facial-brachial-crural hemiparesis is typical of this pathology that regresses over a period of time. The most effective therapeutic approach appears to be a conservative one, although the best treatment regimen is still not well defined. It is necessary to exclude conditions such as heart disease, coagulopathies, and acute traumatic arterial dissections. The authors present a rare case of bilateral basal ganglia infarct in an 18-month-old child following head trauma managed conservatively with good recovery.